Economic Development Strategy of South Lampung Regency Using the Analytical Hierarchy Process Method - Fitri Silvia Amanda; Prayudha Ananta; Emi Maimunah; Nindya Eka Sobita (LPPM STIE Krakatau, 2026)
Purpose: This study aims to determine priority strategies for regional economic development in South Lampung Regency based on the RPJMD 2025–2029, using the Analytical Hierarchy Process (AHP). It focuses on identifying development priorities and analyzing the strategic factors that influence regional economic growth. Methodology: A quantitative descriptive approach was applied through pairwise comparisons of several development criteria, including democracy and law enforcement, good governance, human resource strengthening, equitable development, regional competitiveness, and regional potential. Results: Democracy, security, and law enforcement were the top priorities (19.3%), followed by cultural development, human resource strengthening, and equitable development. Supporting strategies include infrastructure, investment, tourism, and local economic sectors, such as agriculture and MSMEs. Conclusions: Sustainable regional economic development requires synergy among social stability, governance reform, infrastructure development, and optimization of regional potential. Limitations: The study is limited to the AHP analysis of selected RPJMD 2025–2029 indicators. The results are influenced by respondents’ subjective judgments and may not fully capture all socioeconomic conditions. Contribution: This study provides priority-based economic development strategies to assist local governments in formulating effective, sustainable, and evidence-based development policies in South Lampung Regency.